ANALISIS PERSEPSI PENYAKIT TERHADAP KUALITAS HIDUP PASIEN DIABETES MELITUS TIPE II DI RUMAH SAKIT UMUM DAERAH TORABELO - Amelia Rumi; Adifa Salsabila (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2023)
Diabetes mellitus is a disorder that occurs in heterogeneous metabolism due to chronic glycine. Diabetes mellitus also occurs due to disorders in insulin secretion or impaired insulin effect or both factors. Based on the results of the research of the Central Sulawesi Health Office, especially in Sigi Regency, the number of people with type II diabetes mellitus is 15,244 people suffering from type II diabetes mellitus. The purpose of this study was to determine the relationship of the perception of disease in the quality of life of patients with type II diabetes mellitus in the Torabelo regional hospitals. This study used a cross sectional method with the number of respondents, namely 100 respondents, data collection using disease perception questionnaires and live quality questionnaires provided to respondents directly. The results of the study that were obtained from disease perception questionnaires for positive categories, namely 70%, the neutral category of 20% and the negative category of 10%, while the result of life quality cakes are obtained by the category of good 12%, and 88% poor. The results of the chi square test received p = 0.028 or < a (0.05), Ha accepted was rejected meaning to having a relationship between illness perception of the disease of patients with the type II diabetes mellitus. The conclusion was obtained from this study, namely there is a relationship between the perception of disease with the quality of life. The occurrence of increased quality of life due to good disease perceptions.